A Micromachined Piezoresistive Pressure Sensor with a Shield Layer - Gang Cao; Xiaoping Wang; Yong Xu; Sheng Liu (Sensors, 2016)
This paper presents a piezoresistive pressure sensor with a shield layer for improved stability. Compared with the conventional piezoresistive pressure sensors, the new one reported in this paper has an n-type shield layer that covers p-type piezoresistors. This shield layer aims to minimize the impact of electrical field and reduce the temperature sensitivity of piezoresistors. The proposed sensors have been successfully fabricated by bulk-micromachining techniques. A sensitivity of 0.022 mV/V/kPa and a maximum non-linearity of 0.085% FS are obtained in a pressure range of 1 MPa. After numerical simulation, the role of the shield layer has been experimentally investigated. It is demonstrated that the shield layer is able to reduce the drift caused by electrical field and ambient temperature variation.